Understanding Consumer Acceptance of Renewable Energy Services: Insights from Behavioral Economics in Everyday Energy Use - Fajri Hatim; Muhandis Difa'iy Aziz; Firayani Firayani (PT. Anagata Sembagi Education, 2025)
The energy transition has increased the availability of renewable energy services at the household level; however, consumer acceptance remains lower than technological potential. This study aims to examine the influence of behavioral economics factors on consumer acceptance of renewable energy services in everyday energy use. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM–PLS) with data collected from 220 household consumers. The study analyzes behavioral bias and social norms as independent variables and consumer acceptance as the dependent variable. The results reveal that behavioral bias has a negative and significant effect on consumer acceptance, while social norms exert a positive and significant influence. These findings confirm that household energy decisions are not purely rational but are shaped by psychological tendencies and social dynamics. This study highlights the importance of incorporating behavioral economics perspectives to better explain consumer behavior and to design more effective and behaviorally responsive renewable energy policies and services.